"Being an Existential Therapist": An I.P.A Study of Existential Therapists' Experiences (Existential Analysis: Journal of the Society for Existential Analysis, 2006)
There appears to be a trend in the literature to try and distinguish the nature and aims of existential psychotherapy. In some ways this seems to run counter to the more traditional position on existential therapy that asserts that every therapist's style is unique and therefore the nature and aims of therapy are inevitably individualised. This study contributes to these recent developments as it explores the experiences of therapists in relation to their practice and such issues as dialogue, relationship, process and use of underlying philosophies. As well as the expected differences between therapists experiences, this study also found areas of common experiences of practice and the use of theory.